Seismic Assessment of Masonry Minarets under Different Earthquakes - Eronat, Şule Sekin; Sayın, Erkut; Ozmen, Alper (My University, 2024)
Minarets are tall and slender structures and form important elements of mosques. Most historical minarets are constructed with masonry (brick or stone units), while modern minarets typically use reinforced concrete. Recent earthquakes have shown that the majority of these structures are highly susceptible to seismic excitation leading to a range of structural damage, from minor cracking to complete collapse. In this paper, the seismic response of a representative masonry minaret was investigated using acceleration records of the 1999 Kocaeli, 2003 Bingöl and 2011 Van earthquakes. All acceleration records were scaled according to the location of the minaret. For this purpose, a representative masonry minaret that is thought to have been built in the city's central part of Elazığ, Turkey was chosen. After the seismic analysis, displacement and stress values obtained on the minaret were presented. It was seen that the displacements were increased along the height of the minaret. Also, the maximum and minimum stress values were obtained between the cylindrical body and transition segment of the minaret in accordance with the damage zones in the past earthquakes.
Keywords: Finite element modelling; Masonry minaret; seismic response